Gain-of-Function Properties of a Dynamin 2 Mutant Implicated in Charcot-Marie-Tooth Disease - Tassin, Tara C.; Barylko, Barbara; Hedde, Per Niklas; Chen, Yan; Binns, Derk D.; James, Nicholas G.; Mueller, Joachim D.; Jameson, David M.; Taussig, Ronald; Albanesi, Joseph P. (Frontiers in Cellular Neuroscience, 2021)
Mutations in the gene encoding dynamin 2 (DNM2), a GTPase that catalyzes membrane constriction and fission, are associated with two autosomal-dominant motor disorders, Charcot-Marie-Tooth disease (CMT) and centronuclear myopathy (CNM), which affect nerve and muscle, respectively. Many of these mutations affect the pleckstrin homology domain of DNM2, yet there is almost no overlap between the sets of mutations that cause CMT or CNM. A subset of CMT-linked mutations inhibit the interaction of DNM2 with phosphatidylinositol (4,5) bisphosphate, which is essential for DNM2 function in endocytosis. In contrast, CNM-linked mutations inhibit intramolecular interactions that normally suppress dynamin self-assembly and GTPase activation. Hence, CNM-linked DNM2 mutants form abnormally stable polymers and express enhanced assembly-dependent GTPase activation. These distinct effects of CMT and CNM mutations are consistent with current findings that DNM2-dependent CMT and CNM are loss-of-function and gain-of-function diseases, respectively. In this study, we present evidence that at least one CMT-causing DNM2 mutant (ΔDEE; lacking residues 555DEE557) forms polymers that, like the CNM mutants, are resistant to disassembly and display enhanced GTPase activation. We further show that the ΔDEE mutant undergoes 2-3-fold higher levels of tyrosine phosphorylation than wild-type DNM2. These results suggest that molecular mechanisms underlying the absence of pathogenic overlap between DNM2-dependent CMT and CNM should be re-examined.